Measurement Equivalence of Four Psychological Questionnaires in Native-Born Germans, Russian-Speaking Immigrants, and Native-Born Russians. (July 2013) - Hirsch, Oliver; Donner-Banzhoff, Norbert; Bachmann, Viktoria
Psychological constructs depend on cultural context. It is therefore important to show the equivalence of measurement instruments in cross-cultural research. There is evidence that in Russian-speaking immigrants, cultural and language issues are important in health care. We examined measurement equivalence of the Patient Health Questionnaire-9 (PHQ-9), the Patient Health Questionnaire-15 (PHQ-15), the Hamburg Self-Care Questionnaire (HamSCQ), and the questionnaire on communication preferences of patients with chronic illness (KOPRA) in native-born Germans, Russian-speaking immigrants living in Germany, and native-born Russians living in the former Soviet Union (FSU). All four questionnaires fulfilled requirements of measurement equivalence in confirmatory factor analyses and analyses of differential item functioning. The Russian translations can be used in Russian-speaking immigrants and native-born Russians. This offers further possibilities for cross-cultural research and for an improvement in health care research in Russian-speaking immigrants in Germany. The most pronounced differences occurred in the KOPRA, which point to differences in German and Russian health care systems.